2019
DOI: 10.1016/j.autrev.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the treatment of Rheumatoid Arthritis

Abstract: Rheumatoid Arthritis (RA) is a chronic inflammatory disease characterized by a heterogeneous clinical response to the different treatments. Some patients are difficult to treat and do not reach the treatment targets as clinical remission or low disease activity. Known negative prognostic factors, such as the presence of auto-antiantibodies and joint erosion, the presence of a genetic profile, comorbidities and extra-articular manifestations, pregnancy or a pregnancy wish may concur to the treatment failure. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 133 publications
1
88
0
9
Order By: Relevance
“…Another RA-associated gene HLA-DRB1 (Major Histocompatibility Complex, Class II, DR Beta 1) was also a methylation biomarker (cg27107292) detected in this study (Conigliaro et al, 2019;Okada et al, 2019). HLA-DRB1 was one of the first few RA biomarkers discovered four decades ago and harbored more than 100 RA-associated loci (Okada et al, 2019).…”
Section: Biological Observations Of Methylomic Biomarkerssupporting
confidence: 56%
“…Another RA-associated gene HLA-DRB1 (Major Histocompatibility Complex, Class II, DR Beta 1) was also a methylation biomarker (cg27107292) detected in this study (Conigliaro et al, 2019;Okada et al, 2019). HLA-DRB1 was one of the first few RA biomarkers discovered four decades ago and harbored more than 100 RA-associated loci (Okada et al, 2019).…”
Section: Biological Observations Of Methylomic Biomarkerssupporting
confidence: 56%
“…The COVID-19 epidemic represents a health emergency that is inevitably affecting the management of a complex disease such as RA [115,116]. As a chronic autoimmune inflammatory disorder, RA carries a higher infectious risk than the general population.…”
Section: Journal Pre-proofmentioning
confidence: 99%
“…Switching from a JAK inhibitor to another one is a different matter. Unmet needs still exist as some patients fail to achieve or maintain clinical remission with biologic agents or JAK inhibitors [26]. If patients fail to respond to a biologic agent, several reports from registry data and observational studies as well as a randomized controlled trial, have suggested that switching to a drug with a different mode of action may improve efficacy, rather than switching to a second drug with a similar mode of action [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%